A taxonomic revision of the Paranoplocephala primordialis (Douthitt) complex (Cestoda: Anoplocephalidae) in voles and squirrels - Haukisalmi, Voitto; Henttonen, Heikki (Zootaxa, 2007)
This study redescribes Paranoplocephala primordialis (Douthitt) in the red squirrel, Tamiasciurus hudsonicus, describes two new, related species of Paranoplocephala Lühe from Microtus and Myodes (syn. Clethrionomys) voles, and summarizes the patterns of their host specificity and geographic distribution, particularly in Alaska and adjacent regions in Canada and north-eastern Siberia. Paranoplocephala nearctica n. sp. and Paranoplocephala alaskensis n. sp. are shown to be slightly, but consistently differentiated host-specific parasites of Myodes rutilus and Myodes gapperi, and Microtus miurus, respectively. The related Paranoplocephala sp. from Microtus oeconomus is also suspected to be specifically distinct, but the available material does not allow a description of a new species. Paranoplocephala primordialis-like cestodes occur widely in rodents in North America, ranging from California to Labrador and Alaska, but also in north-eastern Siberia. The specific identity of the few Eurasian specimens could not, however, be confirmed. Paranoplocephala primordialis-like species seem to be rare in all host species and regions, maximum prevalences being 8%, 3%, 6.5% and 5% for P. primordialis, P. nearctica n. sp., P. alaskensis n. sp. and Paranoplocephala sp., respectively.